Coconut-water as fermentation medium for enzyme production (2): Optimisation of batch shake-flask fermentation - Jailani Salihon,; Jamaliah Md. Jahim,; Ahmad Jaril Asis, (1995)
The enzyme volume yield (nmol L-1) in batch shake-flask fermentations for the production of the enzyme cytochrome p-450 by the yeast Saccharomyces cerevisiae NCYC 754 on a medium based on coconut-water was optimised with respect to the experimental variables temperature (T), shaking rate (RPM) and the initial concentrations of glucose (G), yeast extract (YE) and peptone (P) supplements using a half-replicate 25 factorial and steepest ascent methods to locate the area containing the maximum enzyme volume yield and using a rotatable composite design to find the optimum levels of the experimental variables at the point of maximum yield. It was found that for maximum enzyme volume yield the levels of the variables are as follows: T = 26.8° C, RPM 159 rpm, G = 139.18 gL-1, YE = 17.04 gL-1 and P 6.95 gL-1. Experiments conducted with these optimised levels of variables gave an average enzyme volume yield of 372.62 nmol L-1 with a biomass yield of 16.08 gL-1. The optimised level of P at 695 gL-1 is very much lower than the previously optimised level of P at 11.90 gL-1 in a medium not based on coconut-water while the optimised levels of the other variables remain almost the same. Peptone costs RM158.00 kg-1 at current market price and the lowering of the optimum level of peptone in a fermentation medium based on coconut-water confirms the usefulness of coconutwater as a base for a fermentation medium in this particular fermentation